TRANSFORMATION ANALYSIS ON CAMPAIGN SLOGANS USED BY THE PRESIDENTIAL CANDIDATES OF THE UNITED STATES OF AMERICA - DEWI, VENONCIA IRENE KURNIA (Jurnal Ilmiah Mahasiswa FIB, 2013)
Slogans usually are used to deliver ideas, visions, emotions, and opinions in very short sentences. In their campaign, the presidential candidates all over the world always use certain slogans which show their vision and mission if they are running for Presidential Candidates and also to persuade the voters of the country to give their vote in the presidential Election Day. The researcher wanted to analyze the structure on the campaign slogans used by the presidential candidates of the United States of America from 1992 until 2012 since it affected the people in the country in deciding which candidates to choose. The researcher conducted this research to find out the transformational grammars on campaign slogans used by the presidential candidates of the United States of America.Therefore, the researcher used qualitative approach in this research in which the primary instrument is the researcher herself to collect the data and analyze the data. The data of this research were 10 campaign slogans from the elected president from 1992 to 2012. The data were taken from www.presidentsusa.net.The researcher found that the transformational grammars that were dominantly used on campaign slogans used by the presidential candidates of the United States of America were imperative transformation which used Imp + you + will + VP => VP as the rule of the tree diagram and emphatic transformation which used Emph + X + tense + *** 1** + Y => X + tense + ***1** + Y as the rule of the tree diagram, both of the rules were written by Bornstein, 1977.She also has suggestion for the next researcher to use the theory of functional grammar since campaign slogans had a hidden meaning and the structures which were used in the campaign slogans had the different function in convincing the hearers and the readers. Keywords: tree diagram, transformational grammar, campaign slogans.